AFRICAN MUSIC AND THE CHURCH IN AFRICA by HENRY WEMAN, trans. Eric J. Sharpe, Swedish Institute of Missionary Research, Domkyrkoplan 2, Uppsala, Sweden, 1960. pp. 296 (31 pp. musical transcriptions) Sw. Kr. 32.50. - Jones, A. M. (International Library of African Music, 1961)
pages: 108-109
Keywords: African Music